High-Resolution Assessment of Wastewater Heat Recovery Potential for Urban Decarbonization - Emil Tsanov; Galina Dimova; Ivelina Hinova; Viden Radovanov; Valentina Dimova (Salehan Institute of Higher Education, 2026)
This study assesses the technical potential for wastewater heat recovery in Sofia and its contribution to domestic hot water supply and greenhouse gas reduction. Heat extraction locations were identified using temperature and flow data from the sewer network and the municipal wastewater treatment plant (WWTP) Kubratovo. Temperature thresholds were defined to ensure stable biological treatment ( ≥ 10°C influent) and environmental protection ( ≥ 5°C effluent). Four scenarios were analyzed, considering heat recovery at the WWTP inlet and outlet with ΔT = 2–4 K. The heat recovery potential is evaluated using 15-minute temperature and flow data by applying scenario-specific temperature thresholds, enabling a dynamic assessment that captures real variations in both flow and temperature and explicitly accounts for system shutdown periods. Heat recovery at the WWTP effluent provides higher and more stable yields than at the influent. The potential ranges from 238,536–380,314 MWh/year at the inlet and 264,828–529,705 MWh/year at the outlet. Under the most favorable scenario (effluent, ΔT = 4 K), the recovered heat can supply domestic hot water to over 76,000 households, reducing emissions by more than 200,000 t CO₂/year when replacing natural gas.